The hound of Rowan - Neff, Henry H. (Tapestry, 2007)
After glimpsing a hint of his destiny in a mysterious tapestry, twelve-year-old Max McDaniels becomes a student at Rowan Academy, where he trains in "mystics and combat" in preparation for war with an ancient enemy that has been kidnapping children like him.